1997
DOI: 10.1021/ie960412+
|View full text |Cite
|
Sign up to set email alerts
|

Low-Order Modeling from Relay Feedback

Abstract: There have recently been considerable interests in extensions of PID relay autotuning to modelbased controllers, and this necessitates transfer function modeling from relay feedback. The methods reported in the literature for this purpose require two tuning tests, and their results are approximate in nature. In this paper, exact expressions for the periods and amplitudes of limit cycles under relay feedback are derived for processes which may be modeled by first-order plus dead-time dynamics. This time-domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 8 publications
1
68
0
6
Order By: Relevance
“…Determination of the parameters of an FOTD model from an asymmetric relay experiment has been done in different ways in e.g. Wang et al (1997); Kaya and Atherton (2001); Srinivasan and Chidambaram (2003); Liu and Gao (2008).…”
Section: Asymmetric Relay Feedbackmentioning
confidence: 99%
“…Determination of the parameters of an FOTD model from an asymmetric relay experiment has been done in different ways in e.g. Wang et al (1997); Kaya and Atherton (2001); Srinivasan and Chidambaram (2003); Liu and Gao (2008).…”
Section: Asymmetric Relay Feedbackmentioning
confidence: 99%
“…Based on a single biased relay test, Wang et al 17 gave a FOPDT model, G m 5 1.00e According to the characteristics of the relay response shape obtained from a single biased relay test as in example 1, the proposed Algorithm-U-A is chosen to derive a SOPDT model, resulting in an underdamped model listed in Table 2. For comparison, the Nyquist plots of these models are shown in Figure 8, which indicates again that obviously improved fitting is captured by the proposed SOPDT model, in particu- lar for the referred low frequency range for controller design.…”
Section: Examplementioning
confidence: 99%
“…Luyben 16 discussed the efficiency of obtaining a FOPDT model from an unbiased relay feedback test. Recent papers 17,18 demonstrated that a FOPDT model can represent the frequency response characteristic of low-or high-order processes with desirable accuracy over the phase range of (2p, 0).In view of that a SOPDT model can give better fitting than a FOPDT model for a real high-order process, and the three types of SOPDT model, overdamped, critically damped, and underdamped, can be effectively used to represent the dynamic response characteristics for a wide variety of chemical processes, a systematic on-line identification method is proposed in this article to obtain such a SOPDT model from a single biased/unbiased relay feedback test. The guidelines for model structure selection are established by classifying the relay response shapes from a large number of relay identification tests on these SOPDT models with different parameter settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A system with restricted (low) input resolution and no (average) steadystate offset is bound to cycle (Theorem 1) and the amplitude a of the oscillations is given by the process gain at the frequency of oscillations, e.g. see (10). So far, we have let the system cycle at its "natural" frequency ω L,180 , as given by (11) and (16).…”
Section: How To Mitigate Oscillations Caused By Restricted Input Resomentioning
confidence: 99%